Factors that influence Australian community buildings' sustainable management. Issue 1 (16th January 2017) - Kalutara, Pushpitha; Zhang, Guomin; Setunge, Sujeeva; Wakefield, Ron
Abstract : Purpose: Australia has a huge stock of community buildings built up over decades. Their replacements consume a large sum of money from country's economy which has called for a strategy for their sustainable management. For this, a comprehensive decision-making structure is an utmost requirement. The purpose of this paper is to capture their sustainable management from four aspects, i.e. environmental, economic, social and functional. Design/methodology/approach: The design process follows an extensive review of environmental and life cycle assessments and company context documents. Extracted factors are tailored to community buildings management following expert consultation. However, the resulted list of factors is extremely large, and "factor analysis" technique is used to group the factors. For this, an industry-wide questionnaire across Australian local councils is employed to solicit opinions of the list of factors. Findings: The analysis has pinpointed 18 key parameters (criteria) to represent all four aspects. This paper presents the preliminary findings of the factors and the analysis results based on the questionnaire responses. Practical implications: The final decision-making structure incorporates all these aspects and criteria. This can be used to develop a decision-making model which produces a sustainability index for building components. Asset managers can mainly use the sustainability index to prioritise their maintenance activities and eventually, to find out cost-optimisation options for them. Originality/value: Most notably, this is the first study to apply all four sustainability aspects (environmental, economic, social and functional) to develop a decision-making structure for Australian community buildings' sustainable management.